THE EFFECTS OF ISLAMIC MICROFINANCING, HUMAN CAPITAL AND ICT USAGE ON WOMEN MICRO-ENTREPRENEURS’ PERFORMANCE IN MALAYSIA - Nur Hazirah Binti Hamdan; Salina Hj Kassim (Journal of Islamic Monetary Economics and Finance, 2022)
This study examines the influences of Islamic microfinancing, human capital development, and information and communication technology (ICT) usage on the performance of Malaysian women micro-entrepreneurs funded by an Islamic microfinance institution (IMFI). It considers Amanah Ikhtiar Malaysia (AIM) as the study setting and adopts a quantitative approach involving 120 women micro-entrepreneurs. The questionnaire was distributed to women micro-entrepreneurs in Selangor state employing a convenience sampling method. The model was analysed utilising the partial least squares structural equation model (PLS-SEM). The findings indicate that Islamic microfinancing, human capital, and ICT usage positively influence the performance of women micro-entrepreneurs. The empirical findings enhance the literature by extending the resource-based view (RBV), a soft theory in the organisational theory literature, by incorporating Islamic microfinancing in the context. It is hoped the study will assist IMFIs and governments in strengthening infrastructures, developing comprehensive business strategies, and educating women micro-entrepreneurs about the possibilities of the digital economy for long-term business sustainability and development.